Contiguous gene deletion of TBX5 and TBX3 leads to a varible phenotype with combined features of holt‐oram and ulnar‐mammary syndromes. Issue 7 (24th May 2013) - Alby, Caroline; Bessieres, Bettina; Bieth, Eric; Attie‐Bitach, Tania; Fermont, Laurent; Citony, Isabelle; Razavi, Ferechté; Vekemans, Michel; Escande, Fabienne; Manouvrier, Sylvie; Malan, Valérie; Amiel, Jeanne
Abstract We report on a combination of congenital malformations in a mother and her fetus harboring a heterozygous deletion encompassing the TBX5 and TBX3 genes, which are disease‐causing in Holt‐Oram and ulnar‐mammary syndromes, respectively. This contiguous gene syndrome is reminiscent of Okihiro syndrome and emphasizes the importance of array‐CGH as a diagnostic tool in atypical syndromic presentations with intrafamilial variability. © 2013 Wiley Periodicals, Inc.